Penerapan Pembelajaran Tematik dalam Membentuk Karakter Gotong Royong pada Siswa Sekolah Dasar - Julkifli Julkifli; Muh. Irfan (Medan Resource Center, 2023)
This study aims to describe the application of thematic learning in forming the mutual cooperation character of elementary school students. The research method uses a qualitative descriptive with a phenomenological design. The research subjects were school principals, teachers, and students. Data analysis uses Miles and Huberman, namely data collection, data reduction, data display and conclusion or verification. The results of the research show that the application of thematic learning in forming the character of mutual cooperation through habituation, communication and exemplary activities can form the mutual cooperation character of students very well in every process of teaching and learning activities in class. Factors supporting and inhibiting the application of thematic learning in shaping the character of students' mutual cooperation include Supporting factors due to the existence of complete infrastructure, the cooperation of the teacher component, the independence and cooperation of students in each teaching and learning activity. Inhibiting factors are due to the large number of learning tools provided in learning, many students in the class, the lack of infrastructure can hinder the process of forming the character of mutual cooperation and teaching and learning activities in class.